CULTIVATION THEORY SEBUAH PERSPEKTIF TEORITIK DALAM ANALISIS TELEVISI - Prijana Hadi, Ido (Institute of Research and Community Outreach - Petra Christian University, 2007)
Cultivation analysis focused attention on television viewing of general consequences of television audience in a long period of time. Cultivation theory strove to understand and explain television dynamics as characteristic and strength of dominant cultures nowadays. Cultivation analysis applied a survey instrument that administratively represented respondents. Responses of television viewing were analyzed using variables of demography including gender%2C age%2C race%2C education%2C income%2C and political views %28liberal%2C moderate%2C and conservative%29. The cultivation analysis was a part of cultural indicators in a project research of Gerbner and his colleagues in which cultural indicators were data about reports related to reality conceptions through television viewing on any particular program. %0D%0AIn other words%2C violence behavior as shown in television was reflection of events around us. If the violence acts reflected legal rules that could not cope with situations as depicted in television acts%2C it could be the real ones. Violence that was presented on television considered as violence that took place in the world. The applicable legal rules to cope with criminal behaviors presented on television could be stated such as the case with our laws. Analysis of television cultivation therewith provided cultural homogenization or cultivation both in mainstreaming and resonance. Abstract in Bahasa Indonesia : analysis+of+cultivation%2C+mainstreaming%2C+resonance